Cost-effectiveness of stereotactic body radiotherapy versus conventional radiotherapy for the treatment of surgically ineligible stage I non-small cell lung cancer in the Brazilian public health system - Gustavo Viani Arruda; Marina Lourenção; Jorge Henrique Caldeira de Oliveira; Julia Simões Correa Galendi; Alexandre Arthur Jacinto (Elsevier, 2022)
Summary: Background: The Brazilian public health system does not pay for the use of Stereotactic body radiotherapy (SBRT) due to its costs and the absence of cost-effectiveness analysis showing its benefit. The present study aims to evaluate whether the SBRT is a more cost-effective strategy than the conventional fractionated radiotherapy (CFRT) for surgically ineligible stage I non-small cell lung cancer (NSCLC) in the Brazilian public health system. Methods: Adopting the perspective of the Brazilian Unified Healthcare System (SUS) as the payer, a Markov model with a lifetime horizon was built to delineate the health states for a cohort of 75-years-old men with medically inoperable NSCLC after treatment with SBRT or CFRT. Transition probabilities and health states utilities were adapted from the literature. Costs were based on the public health system reimbursement values and simulated in the private sector. Findings: The SBRT strategy results in more quality-adjusted life-year (QALYs) and costs with an incremental cost-effectiveness ratio (ICER) of R$ 164.86 (U$ 65.16) per QALY and R$ 105 (U$ 41.50) per life-year gained (LYG). This strategy was cost-effective, considering a willingness-to-pay of R$ 25,000 (U$ 9,881.42) per QALY. The net monetary benefit (NMB) was approximately twice higher. The outcomes were confirmed with 92% of accuracy in the probabilistic sensitivity analysis. Interpretation: Using a threshold of R$25,000 per QALY, SBRT was more cost-effective than CFRT for NSCLC in a public health system of an upper-middle-income country. SBRT generates higher NMB than CFRT, which could open the opportunity to incorporate new technologies. Funding: Varian Medical Systems.